CDK inhibitors for muscle stem cell differentiation and self-renewal - Amrudha Mohan; Atsushi Asakura (Japanese Society of Physical Fitness and Sports Medicine, 2017)
Regeneration of muscle is undertaken by muscle stem cell populations named satellite cells which are normally quiescent or at the G0 phase of the cell cycle. However, upon signals from damaged muscle, satellite cells lose their quiescence, and enter the G1 cell cycle phase to expand the population of satellite cell progenies termed myogenic precursor cells (MPCs). Eventually, MPCs stop their cell cycle and undergo terminal differentiation to form skeletal muscle fibers. Some MPCs retract to quiescent satellite cells as a self-renewal process. Therefore, cell cycle regulation, consisting of satellite cell activation, proliferation, differentiation and self-renewal, is the key event of muscle regeneration. In this review, we summarize up-to-date progress on research about cell cycle regulation of myogenic progenitor cells and muscle stem cells during embryonic myogenesis and adult muscle regeneration, aging, exercise and muscle diseases including muscular dystrophy and muscle fiber atrophy, especially focusing on cyclin-dependent kinase inhibitors (CDKIs).